Tinguian high school dropouts evolving intervention strategies - Alzate, Michelle Melinda Ballo- (2007)
This study aimed to develp a guidance program for Tinguian students who are vulnerable to dropping out. It explored the perceptions of three groups of respondents which include Tinguian high school dropouts and potential drop outs; administrators, counselors, and teachers; and former dropout, fresh dropout, and potential dropout interviewees on the influences to their decision to leave school using questionnaires and case study. It was found that based on students' perception, personal conditions primarily mischievous behavior was their greatest influence for dropping out; for administrators, the prime contributor was socioenvironmental in nature, primarily the longingness for family. A guidance program which aims to contribute to their holistic development was conceptualized